Atuação e formação docente na educação básica diante da pandemia da Covid-19 : um estudo de caso na perspectiva decolonial - Moraes, Denise Machado (My University, 2023)
This dissertation is a qualitative research about the performance and training of teachers in Basic Education in the face of the Covid-19 pandemic: a case study in the Decolonial perspective. The problem addressed in this research was to analyze how the Decolonial perspective can constitute horizons for teaching in Basic Education in the face of the challenges and possibilities from the pandemic. The general objective was to analyze the challenges and possibilities of teaching in Basic Education, in the Municipal Public Network of Caxias do Sul, in times of the Covid-19 pandemic, from possible horizons of the Decolonial perspective. Among the specific objectives, the aim was to characterize education in the face of the impacts caused by the Covid-19 pandemic; recognize in theoretical studies some of the contributions that decoloniality can offer to the improvement of teacher training, pointing out possibilities from the decolonial perspective for teacher training from the Covid-19 pandemic period; to investigate public policies for the continuing education of teachers in the Municipal Public Network of Caxias do Sul, in the decolonial perspective before and during the pandemic, as well as to point out possibilities for Basic Education in the Municipal Public Network, in the sense of carrying out the teaching work during the pandemic and post-pandemic period. Reconstructive Hermeneutics was the methodological conception that guided this research, which is anchored in the dialogue and speech of teachers and is based on the expression of the lived experience from the period of the Covid-19 pandemic in the year 2020, considering as a context the educational environment. A Case Study was carried out in a school in the city of Caxias do Sul/RS; it was decided to work with the construction of data that would be analyzed from a semi-structured questionnaire made available through Google Forms® and with Dialogue Circles. The research corpus was approximately 40 teachers who made up the staff of the analyzed school. In the questionnaire stage and, later, for the Dialogue Circles, three groups of teachers were organized: one of the groups was composed of the school management team and sectors. The other group was organized with the participation of teachers from specialized areas, such as Physical Education, Arts, History, Geography, Mathematics, among other subjects. Finally, one of the groups was formed by teachers seen as a reference for each class, who work from Kindergarten and/or Early Years of Elementary School to 5th Year. Three major categories were analyzed, among them: Characterizing education in the face of the impacts caused by the Covid-19 pandemic; Continuing training of teachers from the Municipal Public Network of Caxias do Sul, during the pandemic; and Possibilities for Basic Education, from the Municipal Public Network, in the sense of the effectiveness of teaching work from the period of the pandemic and post-pandemic. This investigation is based on a decolonial perspective, having as main authors Paulo Freire, Catherine Walsh, Enrique Dussel, among others. The results found point to an increase in the overload of teaching work from the period of the Covid-19 pandemic, which, in some cases, can even converge to the illness of these subjects. In addition, there was a need for basic education institutions to have clear policies regarding the confrontation of the impacts of Covid-19, as well as to invest in reducing the bureaucracy of teaching and in pedagogical training that, in addition to other important factors, prioritize the dialogue and appreciation of teaching subjects. [resumo fornecido pelo autor]
Esta dissertação constitui-se em uma pesquisa qualitativa acerca da atuação e da formação docente na Educação Básica diante da pandemia da Covid-19: um estudo de caso na perspectiva Decolonial. O problema trabalhado nesta pesquisa foi o de analisar de que forma a perspectiva Decolonial pode constituir horizontes à docência na Educação Básica frente aos desafios e possibilidades a partir da pandemia. O objetivo geral foi analisar os desafios e possibilidades da docência na Educação Básica, na Rede Pública Municipal de Caxias do Sul, em tempos de pandemia da Covid-19, a partir de possíveis horizontes da perspectiva Decolonial. Entre os objetivos específicos, almejou-se caracterizar a educação frente aos impactos ocasionados pela pandemia da Covid-19; reconhecer nos estudos teóricos algumas das contribuições que a decolonialidade pode oferecer para o aprimoramento da formação docente, pontuando possibilidades da perspectiva decolonial para formação docente a partir do período de pandemia da Covid-19; investigar as políticas públicas para a formação continuada de professores da rede pública municipal de Caxias do sul, na perspectiva decolonial antes e durante a pandemia, bem como pontuar possibilidades para a Educação Básica da Rede Pública Municipal, no sentido da efetivação do trabalho docente durante o período da pandemia e pós-pandemia. Esta pesquisa pretende contribuir para o entendimento acerca da docência na Educação Básica frente aos desafios e possibilidades a partir da pandemia da Covid-19, especialmente na escola pesquisada. A Hermenêutica Reconstrutiva foi a concepção metodológica que norteou esta pesquisa, a qual está ancorada no diálogo e na fala dos docentes e tem como base a expressão da experiência vivida a partir do período da pandemia da Covid-19 no ano de 2020, considerando como contexto o meio educacional. Realizou-se um Estudo de Caso em uma escola da cidade de Caxias do Sul/ RS; optou-se por trabalhar com a construção de dados que seriam analisados a partir de um questionário semiestruturado disponibilizado por meio do Google Forms® e com Círculos de Diálogos. O corpus da pesquisa foram os cerca de 40 professores que compunham o quadro funcional da escola analisada. Na etapa do questionário e, posteriormente, para os Círculos de Diálogos, foram organizados três grupos de docentes: um dos grupos foi composto pela equipe de gestão da escola e setores. O outro grupo foi organizado contando com a participação dos professores de áreas especializadas, como Educação Física, Artes, História, Geografia, Matemática, entre outras disciplinas. Por fim, um dos grupos foi formado pelos professores vistos como referência de cada turma, que atuam desde a Educação Infantil e/ou Anos Iniciais de Ensino Fundamental até 5° Ano. Três grandes categorias foram analisadas, entre elas: Caracterizar a educação frente aos impactos ocasionados pela pandemia da Covid-19; A formação continuada de professores da Rede Pública Municipal de Caxias do Sul, durante a pandemia; e Possibilidades para a Educação Básica, da Rede Pública Municipal, no sentido da efetivação do trabalho docente a partir do período da pandemia e pós-pandemia. Esta investigação está embasada a partir de uma ótica decolonial, tendo como autores Paulo Freire, Catherine Walsh, Enrique Dussel, entre outros. Os resultados encontrados apontam para um aumento da sobrecarga de trabalho docente a partir do período da pandemia da Covid-19, o que, em alguns casos, pode convergir até para o adoecimento desses sujeitos. Além disso, observou-se a necessidade de as instituições de educação básica terem claras as políticas referentes ao enfrentamento dos impactos da Covid-19, bem como investirem na desburocratização do fazer docente e em formações pedagógicas que, além de outros fatores importantes, priorizem o diálogo e a valorização dos sujeitos docentes. [resumo fornecido pelo autor]
Keywords: Professores - Formação; Educação; COVID-19; Teachers - In-service training; Education; COVID-19